Establishing a Partnership Instrument for Cooperation with Third Countries (2011)
This proposal for a Partnership Instrument replaces the financing Instrument for Cooperation with Industrialised and other high income countries and territories (ICI)1, which came into force in 2007, and which has been the EU’s main vehicle for collaboration with developed countries. The ICI has proved an effective toolbox for providing a differentiated and appropriate response to widen and deepen the cooperation with 17 countries (industrialised countries and high-income territories in North America, the Asia-Pacific region and the Gulf region). It has been recently extended to developing countries with the adoption of the ICI+ proposal. However, as it is due to expire by the end of 2013; a new financial instrument is needed.